2022
DOI: 10.1017/s1047951122000671
|View full text |Cite
|
Sign up to set email alerts
|

Electric toy car to reduce anxiety before a cardiac catherisation: randomised controlled trial

Abstract: Background: Anxiety before an invasive intervention is associated in children with persistent psychological disorders. We studied the effect of the transfer to the catheterisation room by an electric toy car on the anxiety of children and their parents before a cardiac catheterisation. Methods: Forty-eight children with a median age of 5.6 years [4.2–7.0] were randomised to either riding on an electric car to go to the catheterisation laboratory or being transported lying supine on a gur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…The study concludes that the use of distraction in the form of playing with play dough facilitated the administration of oral midazolam in young children. More studies that used electric cars without integrated interventions showed that riding an electric toy car decreased anxiety in kids and their parents [5,14].…”
Section: Related Workmentioning
confidence: 99%
“…The study concludes that the use of distraction in the form of playing with play dough facilitated the administration of oral midazolam in young children. More studies that used electric cars without integrated interventions showed that riding an electric toy car decreased anxiety in kids and their parents [5,14].…”
Section: Related Workmentioning
confidence: 99%